2014
DOI: 10.1515/ijamh-2013-0306
|View full text |Cite
|
Sign up to set email alerts
|

School-based intervention to promote healthy nutrition in Sousse, Tunisia

Abstract: Introduction: Obesity among children is a major risk factor for chronic diseases. School interventions programs can represent a mean to implement healthy nutrition attitudes at early ages. Our objective was to evaluate the effects of a school intervention program to promote healthy nutrition among adolescents, in terms of knowledge, behaviors and intention. Methods: Quasi experimental study among urban students in Sousse, Tunisia with 2 groups, intervention and control. The intervention group had an interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
2
19
1
1
Order By: Relevance
“…Although a significant number of school-based studies look into modifying nutrition and physical activity behaviors to combat the obesity problem in developed countries, only a handful have been conducted in the developing world. In Tunisia, a school-based study on nutrition promotion is the only other known study on the topic ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant number of school-based studies look into modifying nutrition and physical activity behaviors to combat the obesity problem in developed countries, only a handful have been conducted in the developing world. In Tunisia, a school-based study on nutrition promotion is the only other known study on the topic ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Five interventions reportedly targeted more than one setting: school and family [54,56], preschool and family [59], school and community [52], and school, family and community [60]. Included interventions addressed physical activity ( n = 12) [47,48,49,53,54,55,56,59,60,61,62,63], dietary behaviour ( n = 6) [46,48,49,59,60,64,65], and eight reported on anthropometric outcomes [52,53,54,55,60,62,63,66]. Only one intervention [59] targeted preschool-age children, while all others targeted school-age children.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions included curriculum changes [48,53,54,55,62], additional sessions of physical activity or physical education [46,47,48,49,53,54,59,60,61,63,64,66], additional teaching around healthy eating and lifestyles in general [46,47,48,49,52,53,54,59,60,64,65], providing training or materials to teachers or parents [46,47,53,54,55,56,59,60,62,64], organising sports tournaments or leagues [48,60,63], providing or improving school meals [52], and changing different aspects of the school environment [46,47,52,56,60,62,64]. All but one intervention involved several different components, the exception being a low-cost physical activity promotion intervention that primarily involved providing sports equipment, toys, and upgrades to the school playground in order to stimulate more free play [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline results indicate an important proportion of low physical activity, tobacco use, overweight and obesity. The effectiveness of the three years' intervention program in students of Sousse Tunisia has been evaluated in previous studies 15 – 18 . Tracking the effects of the intervention in schools a year after its achievement has shown that it still has some positive effects.…”
Section: Discussionmentioning
confidence: 99%